2017
DOI: 10.1371/journal.pone.0174681
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of malignant and benign breast lesions: Added value of the qualitative analysis of breast lesions on diffusion-weighted imaging (DWI) using readout-segmented echo-planar imaging at 3.0 T

Abstract: ObjectiveTo determine the added value of qualitative analysis as an adjunct to quantitative analysis for the discrimination of benign and malignant lesions in patients with breast cancer using diffusion-weighted imaging (DWI) with readout-segmented echo-planar imaging (rs-EPI).MethodsA total of 99 patients with 144 lesions were reviewed from our prospectively collected database. DWI data were obtained using rs-EPI acquired at 3.0 T. The diagnostic performances of DWI in the qualitative, quantitative, and combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…Thus far, only a few studies pertaining to DWI have addressed its potential for morphological analysis of breast lesions . Kang et al analyzed the diagnostic accuracy of high peripheral DWI signal in breast lesions, the "rim sign," and reported sensitivity, specificity, and area under the curve (AUC) values equaling 59.7%, 80.6%, and 0.701, respectively .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus far, only a few studies pertaining to DWI have addressed its potential for morphological analysis of breast lesions . Kang et al analyzed the diagnostic accuracy of high peripheral DWI signal in breast lesions, the "rim sign," and reported sensitivity, specificity, and area under the curve (AUC) values equaling 59.7%, 80.6%, and 0.701, respectively .…”
Section: Discussionmentioning
confidence: 99%
“…The investigators also observed higher AUC values based on the BI‐RADS score for rFOV DWI than for bilateral DWI and suggested the additional information on tumor morphology provided by rFOV DWI could have contributed to the increase. Recently, a more comprehensive analysis was provided by An et al, who compared the diagnostic performances of DWI in the qualitative, quantitative, and combination analyses with that of DCE MRI . Lesions were subjected to qualitative DWI analysis using multiple morphological descriptors contained in the current BI‐RADS lexicon edition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in figure 5 and 6 A, B, C&D there was no central enhancement lesion in the present study. 16.2% of the lesions showed dark non enhancing internal septations that are mostly benign type. The least number of lesions are homogeneous types (fig-5).…”
Section: Mass Enhancement Typementioning
confidence: 97%